Induction and Characterization of a Cytochrome P-450-Dependent Camphor Hydroxylase in Tissue Cultures of Common Sage (Salvia officinalis). - Funk, C. (1993)
(+)-Camphor, a major monoterpene of the essential oil of common sage (Salvia officinalis), is catabolized in senescent tissue, and the pathway for the breakdown of this bicyclic ketone has been previously elucidated in sage cell-suspension cultures. In the initial step of catabolism, camphor is oxidized to 6-exo-hydroxycamphor, and the corresponding NADPH- and O2-dependent hydroxylase activity was demonstrated in microsomal preparations of sage cells. Several well-established inhibitors of cytochrome P-450-dependent reactions, including cytochrome c, clotrimazole, and CO, inhibited the hydroxylation of camphor, and CO-dependent inhibition was partially reversed by blue light. Upon treatment of sage suspension cultures with 30 mM MnCl2, camphor-6-hydroxylase activity was induced up to 7-fold. A polypeptide with estimated molecular mass of 58 kD from sage microsomal membranes exhibited antigenic cross-reactivity in western blot experiments with two heterologous polyclonal antibodies raised against cytochrome P-450 camphor-5-exo-hydroxylase from Pseudomonas putida and cytochrome P-450 limonene-6S-hydroxylase from spearmint (Mentha spicata). Dot blotting indicated that the concentration of this polypeptide increased with camphor hydroxylase activity in microsomes of Mn2+-induced sage cells. These results suggest that camphor-6-exo-hydroxylase from sage is a microsomal cytochrome P-450 monooxygenase that may share common properties and epitopes with bacterial and other plant monoterpene hydroxylases.